2020
DOI: 10.1111/jcpp.13243
|View full text |Cite
|
Sign up to set email alerts
|

Factorial invariance in hierarchical factor models of mental disorders in African American and European American youths

Abstract: Background: There is converging and compelling evidence that mental disorders are more optimally conceptualized in a hierarchical framework that transcends traditional categorical boundaries. However, the majority of this evidence comes from studies that draw upon predominantly Caucasian populations. Whether the hierarchical conceptualization of mental disorders generalizes across racial-ethnic groups, including for African American (AA) youths, is unclear. This research is especially crucial in light of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 50 publications
0
14
0
1
Order By: Relevance
“…Patalay et al ( 2015 ) examined the latent structure of a broad set of indicators of psychological distress in a community sample of children aged 11–13 years ( N = 23,477) and found evidence of two broad dimensions of psychopathology (Internalizing and Externalizing), along with the p factor. Subsequent studies with a diverse range of child and adolescent samples have reported similar results, including evidence of subfactors under the Internalizing and Externalizing spectra (Afzali et al, 2018 ; Carragher et al, 2016 ; He & Li, 2021 ; Laceulle et al, 2015 ; Michelini et al, 2019 ).…”
Section: Introductionmentioning
confidence: 78%
“…Patalay et al ( 2015 ) examined the latent structure of a broad set of indicators of psychological distress in a community sample of children aged 11–13 years ( N = 23,477) and found evidence of two broad dimensions of psychopathology (Internalizing and Externalizing), along with the p factor. Subsequent studies with a diverse range of child and adolescent samples have reported similar results, including evidence of subfactors under the Internalizing and Externalizing spectra (Afzali et al, 2018 ; Carragher et al, 2016 ; He & Li, 2021 ; Laceulle et al, 2015 ; Michelini et al, 2019 ).…”
Section: Introductionmentioning
confidence: 78%
“…Previous evidence demonstrates that the CBCL correlated model is invariant across 30 cultures and, therefore, cross-country comparisons can be made (Ivanova et al, 2007). Moreover, previous evidence using different instruments already showed gender, age, and race/ethnicity invariance of bifactor models of psychopathology in youth (Gluschkoff et al, 2019;He & Li, 2021;Pezzoli et al, 2017). However, bifactor models were shown to best represent psychopathology in community rather than clinical samples (Fernández de la Cruz et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Previous evidence demonstrates that the CBCL correlated model is invariant across 30 cultures and, therefore, crosscountry comparisons can be made (Ivanova et al, 2007;Rescorla et al, 2007). Moreover, previous evidence using different instruments already showed gender, age and race/ethnicity invariance of bifactor models of psychopathology in youth (Gluschkoff et al, 2019;He & Li, 2021;Pezzoli et al, 2017). However, bifactor models were shown to best represent psychopathology in community rather than clinical samples (Fernández de la Cruz et al, 2018).…”
Section: Discussionmentioning
confidence: 99%